What is the financial feasibility for the structure a network of reverse logistics for recovery solid waste in the marines the colombian national territory (2014)
In a globalized world very fast and very demanding markets changes, makes countries through its companies are increasingly competitive, with a greater increase in production management that should be suitable for raw materials and finished products or developed, making it necessary to integrate a new approach to corporate environmental practices such as proactive management strategy of organizations.